Vulnerability in Colorectal Cancer: Adjusted Gross Income and Geography as Factors in Determining Overall Survival in Colorectal Cancer: A Single-Center Study Across a Broad Income Inequality in an American Context - Cataldo Doria; Patrick G. De Deyne; Papachristou Charalampos (Current Oncology)
Introduction: Regional differences in socioeconomic status (SES) are well known, and we believe that the use of geocoding (zip code) can facilitate the introduction of targeted interventions for underserved populations. This is a single-center, retrospective analysis of data extracted from the cancer registry at the Capital Health Cancer Center in Pennington, N. The Capital Health Cancer Center in central New Jersey primarily serves two counties, catering to a diverse patient population from a wide range of socioeconomic backgrounds. Methods: We abstracted 1269 consecutive cases of colorectal cancer (CRC) diagnosed and treated between 2000 and 2019 from the Cancer Registry of the Capital Health Cancer Center (CHCC). Using the definition of SES based on previously published work, and zip codes (geocoding), we created four SES levels. We stratified our subjects according to their stage at diagnosis, age at diagnosis, race, and ethnicity. The primary outcome variable was overall survival (OS). Results: There was a statistically significant difference in OS based on SES, with the highest overall survival (OS) in the high-SES group (47 months) and the shortest OS in the low and mid-low-SES groups (40.4 and 30 months, respectively). Subjects living in high-SES areas were predominantly white (88.2%) and diagnosed at a later age (mean of 68.9 years of age) compared to individuals who lived in a low-SES area, who were predominantly non-white (72.6%) and diagnosed somewhat earlier in life (65.1 years of age). White people were diagnosed later in life (70.9 years of age) compared to non-white populations, including Black (66.5), Asian (61.7), and Hispanic (58.5) (p = 0.001) populations, but this did not lead to a significant difference in OS (p = 0.56). Stage at diagnosis was a significant predictor of OS, but was unrelated to SES (p = 0.066). A Cox proportional hazard ratio (HR) model showed that the risk of dying from colorectal cancer decreases with a higher socioeconomic status (SES). Those from mid-high-SES backgrounds had a 19% lower risk (HR 0.81), and those from high-SES areas had a 45% lower risk (HR 0.55) compared to individuals from low-SES areas. Conclusions: The vulnerability of patients with CRC in central New Jersey is a complex issue, influenced by many different variables. Our results indicate that SES is the most critical factor affecting OS after being diagnosed with CRC.